Antikoagulation bei Vorhofflimmern - Hohnloser, Stefan (DMW - Deutsche Medizinische Wochenschrift, 2020)
Anticoagulation with oral antagonists without vitamin K (NOACs) is the preferred therapy for stroke prevention in atrial fibrillation. Vitamin K antagonists (VKA) should only be prescribed if there are contraindications to NOAC (e. g. mechanical heart valves, rheumatic mitral stenosis). The guideline recommendations are based on dedicated NOAC development programs with large randomized clinical phase III studies. Data from observational studies on the efficacy and safety of NOACs compared to VKA are in general complementary to data stemming from the phase III studies. Due to their pharmacokinetic and dynamic properties, NOACs are much easier to handle than VKA. Amongst other advantages, this implies that in case of short interruptions in anticoagulation therapy (e. g. for surgical procedures), bridging therapy with heparin is no longer required. This will reduce bleeding complications dramatically.
Keywords: Vorhofflimmern; Schlaganfallprävention; Antikoagulation; NOACs; Blutungsrisiko